Penggunaan Alat Ukur Kecepatan Berbasis Arduino Materi GLB dan GLBB untuk Meningkatkan Keterampilan Berpikir Kritis Siswa SMK - Muhammad Subhan; Eka Rahmawati; Fatimah Fatimah; Lis Suswati; Yus’iran Yus’iran (UNIVERSITAS INDRAPRASTA PGRI, 2023)
Learning about straight motion can be observed in everyday life. The condition of students in the research school where some SMK students find it difficult to understand how to observe objects moving or going so fast, and do not know how to determine the right time. This research is the application of learning using arduino-based infrared sensor media to measure the speed of GLB-GLBB straight motion. The purpose of this study was to see the effect of media in improving students' critical thinking skills. This research is a pre- experimental Data was obtained using 10 number critical thinking essay questions, the results of the pretest and posttest will be converted using a critical thinking instrument grid with 4 criteria, namely: Analyzing skills, synthesizing skills, problem solving skills and concluding skills.Â Critical thinking criteria data were analyzed using the percentage formula to see the percentage level of student skills increase. As for the hypothesis test analysis, the Paired Two Sample for Means t test or paired test was used. The average pretest = 60.9 and the average posttest = 81.8. Critical thinking skills data analysis results from 4 criteria: (1) analyzing skills at pretest = 58.9% and at posttest = 75%; (2) synthesizing skills at pretest = 60.7% and posttest = 85.7%; (3) problem solving skills at pretest = 66.1% and posttest = 76.8% and (4) conclusion skills at pretest = 55.4% and posttest = 83.9%. While the significance test of the analysis results is t-statistic = 7.42 and t-table two-tail = 2.02 so that overall it can be concluded that the use of infrared sensor media based on arduino measuring the speed of GLB-GLBB straight motion can affect and improve the critical thinking skills of SMK students.